Digitalization of the laboratory management module for strengthening the laboratory skills of prospective science teachers - Susanti; Ani Widyawati; Laily Rochmawati Listiyani; Tri Astuti Arigiyati; Tias Ernawati (Jurnal Pijar Mipa, 2023)
The transition to online learning since the start of the Covid-19 pandemic has forced all parties to respond quickly to the use of information technology. Various applications are used in the learning process. Of course, this was followed by the digitization of learning tools, including the Laboratory Management course held by the Science Education Study Program of the University of Sarjanawiyata Tamansiswa. Learning tools are needed to accommodate Course Learning Outcomes (CLO), one of which is a module. The modules are comprehensive, systematic, and accompanied by a planned learning experience designed to help students master the learning objectives. This research is a preliminary stage of research on the digitalization of module products which was carried out using the Borg and Gall models. This study aims to describe the need to develop the digitalization of the Science Laboratory Management course module to strengthen the laboratory skills of prospective science educators. The method used is a literature study of the needs and other considerations related to the development of module products. The study results stated that digitizing the Laboratory Management module makes it easier for students to access materials anywhere and anytime. Learning becomes more focused and structured. The e-module was developed by considering the laboratory skill needs of prospective science educators. The selected laboratory skill indicators include mastery of practical tools, accuracy and accuracy of work, Occupational Safety and Health, and handling of chemicals.